Development of cattle breeding of the Kazakh steppe in the XVIII-XIX centuries in the works of Russian travelers: historiographic analysis (on the example of Semirechye) - Kuketova, А.А. (KU publ., 2020)
The article deals with the actual problem of the development of traditional livestock breeding of the Kazakh people in the works of Russian travelers of the XVIII century. The materials were obtained from primary sources on the basis of the works of Russian travelers, researchers, and from the results of academic expeditions; the study provides a historiographic and a source study analysis of the process of the formation of nomadic and semi-nomadic cattle breeding. The author of the article found out that the development of nomadic cattle breeding of the Kazakh people is influenced by local natural and climatic factors. Also analyzes regional features of the Kazakh steppe economy, which is based on the works of Russian travelers. As a result of the materials of the I and II academic conferences, works were analyzed and conclusions were drawn about the development of traditional animal husbandry of the Kazakh people. Information about cattle breeding in the journals of officials of the Russian Empire is also analyzed. This study presented the works of Russian travelers and researchers of the XVIII century.
XVIII–XIX ғасырдағы қазақ даласындағы мал шаруашылығының дамуы орыс саяхатшыларының еңбектерінде: тарихнамалық талдау (Жетісу өлкесі мысалында)
Развитие скотоводства казахской степи в XVIII–XIX вв. в трудах русских путешественников: историографический анализ (на примере Семиречья)
Keywords: Kazakh steppe; Kazakh people; Russian travelers; officials; animal husbandry; natural and climatic factors; academic expeditions